If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(6+x)=6
We move all terms to the left:
4(6+x)-(6)=0
We add all the numbers together, and all the variables
4(x+6)-6=0
We multiply parentheses
4x+24-6=0
We add all the numbers together, and all the variables
4x+18=0
We move all terms containing x to the left, all other terms to the right
4x=-18
x=-18/4
x=-4+1/2
| -16t^2+16.67+0=15000 | | 7y-7=22 | | 6(-6-x)=-6 | | 9(x-9)-3=4(2+4) | | 4b-56=180 | | 3=12v-v | | 1/3(5+w)=24 | | 5m-1=-2m+6 | | 5m-1=-1m+6 | | 4-2(6)=x | | X+31=4x+14 | | 5m-1=-2+6 | | 17u=32+9u | | w/4-2=15 | | 8x+2(3x-2)=10 | | 5+6x=16x-15 | | -2x-1=-9-1 | | 17=3x+3x-1 | | 7-9m=43 | | 48=6x+7x+9 | | -2x+x=3x-10+x | | 2b=2b-56 | | x-5+6x=72 | | 59=3y÷3 | | 4 | | a/10=7 | | Y+45=3y | | 4x-7+2x-23=180 | | 3c^2+12c+8=0 | | w+73=3w-57 | | 9=r=17 | | 9x-x=3x-54-x |